Neuropeptide modulation of lymphatic smooth muscle tone in the canine forelimb - David E. Dobbins (Mediators of Inflammation)
Neurokinin A and B are putative inflammatory mediators. We assessed their ability to alter prenodal lymphatic resistance. Intralymphatic neurokinin A (3.0 × 10−6, 3.0 × 10−5 and 3.0 × 10−4 mol l−1) significantly constricted lymphatics at the two highest doses. Preliminary experiments suggested that neurokinin B might dilate lymphatics. To test this, lymphatic pressure was increased by norepinephrine (3.1 × 10−6 mol l−1). Neurokinin B (2.7 × 10−4 mol l−1) was then infused intralymphatically during norepinephrine infusion. Norepinephrine increased perfusion pressure from 5.6 ± 0.6 mmHg to 12.1 ± 1.4 mmHg. Subsequent infusion of neurokinin B significantly decreased lymphatic perfusion pressure from 11.9 ± 1.3 mmHg to 9.9 ± 1.1 mmHg. These data indicate that neurokinin A and B can alter lymphatic resistance and are consistent with the hypothesis that lymph vessel function may be subject to modulation by neurokinins.